Randomized evaluation of the loss‐of‐function carboxylesterase 1 (CES1) G143E variant on clopidogrel and ticagrelor pharmacodynamics - Joshua P. Lewis; Kathleen A. Ryan; Elizabeth A. Streeten; Hilary B. Whitlatch; Melanie Daue; Keith Tanner; James A. Perry; Jeffrey R. O'Connell; Alan R. Shuldiner; Braxton D. Mitchell (Clinical and Translational Science)
Abstract Antiplatelet therapy with a P2Y12 receptor inhibitor, in combination with aspirin, is standard of care for medical management of patients with coronary artery disease, and flexibility in prescribing options among these medications offers great potential for individualizing patient care. Previously, we showed that a loss‐of‐function missense mutation (G143E) in carboxylesterase 1 (CES1), the primary enzyme responsible for clopidogrel degradation, significantly impacts on‐clopidogrel platelet aggregation and recurrent cardiovascular event risk. In the current investigation, we conducted a prospective randomized crossover study of clopidogrel (75 mg/day for 7 days) and ticagrelor (180 mg/day for 7 days) in 50 individuals stratified by CES1 G143E genotype (N = 34 143GG and 16 143GE) to determine the effect of drug choice on inhibition of platelet aggregation (IPA). Consistent with prior reports, we observed strong association between G143E and adenosine diphosphate‐stimulated platelet aggregation following clopidogrel administration (IPA = 71.6 vs. 48.0% in 143E‐allele carriers vs. non‐carriers, respectively, p = 3.8 × 10−5). Similar significant effects on platelet aggregation were also noted between 143E‐allele carriers versus non‐carriers in response to stimulation with arachidonic acid (45.8 vs. 25.8%, p = 0.04), epinephrine (44.4 vs. 18.8%, p = 0.03), and collagen (5 μg/mL, 25.8 vs. 11.4%, p = 3.7 × 10−3). In contrast, no relationship between CES1 G143E and IPA was observed following ticagrelor administration regardless of the platelet agonist used. Collectively, these data suggest that on‐clopidogrel platelet aggregation is substantially modified by CES1 G143E genotype, that this variant does not modify ticagrelor pharmacodynamics, and that more consistent inhibition of platelet aggregation may be achieved by using ticagrelor in patients who carry clopidogrel response‐modifying alleles in CES1.